Predictors of success for African black physiotherapy students in South Africa - Mambo-Kekana, Nonceba Priscilla (My University, 2009)
The research reported in this thesis investigated factors that predict academic success of African black physiotherapy students. The first part of the literature review focused on higher education and access into higher education. It refers to the National Plan on Higher Education and the international debate around widening access. Significance within the international literature is that while there has been rapid expansion in higher education numbers there has not been a parallel increase in participation by underrepresented groups. Most of the literature found on predictors of success indicates that high school performance and aptitude tests are predictors of success. It also indicates that the predictive strength of these variables reduces when race is taken into consideration and in physiotherapy it reduces in the clinical years of study. Non-cognitive variables have also been found to predict success. Although many quantitative studies on prediction of academic success have been performed, it was noted in the literature analysis that there is minimal investigation of predictors of success that have been done in the physiotherapy profession. No recent studies were found that pertain to physiotherapy specifically, and the few studies available were found not to have taken race differences into consideration. Throughout South Africa universities that have physiotherapy programmes admit students on the basis of their high school performance. Some of them use other criteria such as involvement in sports, leadership qualities and community involvement. Moreover, most African black students do not have the opportunity to fulfill these criteria and therefore other factors that may predict academic success were investigated. One hundred and twenty eight graduates (66 black and 62 white) who graduated between 2000 – 2005 from eight universities and six Heads of Physiotherapy Departments participated in the research. For the purposes of this study, graduates who completed the degree in four years or four and a half years were defined as successful and those that completed in five years and above were defined as unsuccessful. The graduates responded to a questionnaire which had two sections: Section A had closed ended questions and Section B had open ended questions. Face-to-face, in-depth interviews were conducted with Heads of Departments using semistructured interview schedule. The data were subjected first to simple descriptive statistical analysis. These analyses revealed that 59% of blacks were successful compared to 90% of whites and that there were more successful females than males. The average time taken to complete physiotherapy degree is 5 years for blacks and 4 years for white; black students were less likely to succeed in physiotherapy programmes. Frequency analysis was done using Chi square test and the results showed an association between race and success (X2 = 16.29; p < 0.01). Logistic regression was done and the results revealed that high school performance was not a predictor of success for black students and that sharing a residence room (OR = 3.09; p = 0.05), obtaining information about university support systems from classmates (OR = 6.25; p < 0.05), feeling part of the group of classmates (OR = 3.23; p < 0.05) and choosing physiotherapy as the first choice of career (OR = .33; p < 0.05) were predictors of success of black physiotherapy students. These results indicate that a supportive learning environment is conducive for black students’ academic success Responses to the open ended questions were collated for each question and then analysed using content analysis as described by Mayan (2002). Themes that emerged with regards to student success indicate that according to the respondents, a student who is determined to succeed and become a physiotherapist, who has the support they need (particularly finance and family), and favourable learning environment will be successful in their studies. Themes that emerged regarding factors that are barriers to students’ academic success were: lack of academic discipline, academic problems, psychosocial difficulties, poor learning environment. A question was raised regarding reasons of students leaving the physiotherapy programme before completion. The responses represent secondary data because it was difficult to locate students who had left physiotherapy programmes. The most cited reasons were multiple failures resulting in academic exclusion, and decision to change career. The interviews with the Heads of Department were transcribed verbatim. These transcripts were then subjected to data-reducing procedures described by Tesch (1990). Firstly the analysis confirmed that black students take an average of 5 years to complete the degree and that the failure occurred mainly in first two years of study. The analysis also revealed that there were few (2 – 10) black students admitted into physiotherapy each year particularly at the Historically White Universities although there were additional criteria that sought to widen access for black students. Secondly, themes that emerged regarding factors that are perceived to contribute to students’ academic success indicated that a successful student is a student who has adequate knowledge about the physiotherapy profession, has academic discipline, has all the relevant support needed and is integrated well with classmates. On the other hand, a student who is inadequately prepared for higher education, has poor proficiency of language of instruction, lacks financial support and has difficult social circumstances, will not be successful in his or her studies. The HODs indicated that there are support systems put in place within their departments and the university at large. The support is academic, financial and psychosocial. vi The results of this study have shown that black students are less likely to be successful than white students, and that average time taken to complete the degree is 5 years. According to Graves (2008), in America the gap between black and white graduation rates still exists and it has been found that many colleges and universities graduate black students at significantly lower rates than white students. The immediate reaction to this result in the South African context would be that the reason for this outcome is that most black students are admitted with lower high school performance. The results in this study did indeed show that the distribution of aggregate and per-subject marks was lower for black respondents than for white respondents, and that at these lower ranges there were equal chances of success and failure. In other words, in dealing with black physiotherapy students, one must look beyond the matric results to identify factors that predict success. Uncertainty about the validity of matric as a predictor of further performance has long existed for low-scoring, disadvantaged students from the previous Department of Education and Training’s, black only educational systems. The rapidly changing South African situation complicates the use and evaluation of the use of matric results for selection. A supportive learning environment has proved to be important for success of African black physiotherapy students.
Ph.D. Faculty of Health Sciences, University of the Witwatersrand, 2008
Keywords: physiotherapists; success; black students; South Africa